INTERNET BAGI PEREMPUAN SALAFI: RUANG INTERAKSI DAN EKSPRESI - Murida Yunailis (Penamas, 2019)
Abstract The Salafi Movement is one of the most popular transnational Islamic movements after the fall of the New Order regime. The word salafi in this paper refers to the abbreviation "al-salaf al-salih" which mean is the previous generation. Initially, this movement entered Indonesia along with the return of the scholars who studied in the Middle East before the 20th century. The focus study of this paper is, the author wants to examine the reasons for salafi women using the internet. This research is a qualitative research using library research methods, observations and interviews with 5 participants selected based on purposive sampling. The results obtained are, there are three specific reasons why salafi women use the internet namely; cheaper, practical, and because the majority of people use the internet